The excessive number of free radicals in human body could increase lipid peroxides and causes a variety of degenerative diseases. Piper crocatum is a plant containing natural chemicals that may have an antioxidant ability to inhibit fatty acid oxidation and reduce free radicals, however, there is no published scientific reports up to now. Therefore, the objective of this research is to study the ability of ethanol extract of P. crocatum as an antioxidant. The leaves of P. crocatum (25 g) were ex - MUHAMMAD ALFARABI; MARIA BINTANG; . SURYANI; MEGA SAFITHRI (HAYATI Journal of Biosciences, 2010)
The excessive number of free radicals in human body could increase lipid peroxides and causes a variety of degenerative diseases. Piper crocatum is a plant containing natural chemicals that may have an antioxidant ability to inhibit fatty acid oxidation and reduce free radicals, however, there is no published scientific reports up to now. Therefore, the objective of this research is to study the ability of ethanol extract of P. crocatum as an antioxidant. The leaves of P. crocatum (25 g) were extracted with 100 ml of 70% ethanol. Antioxidant activity was measured by thiobarbituric acid method and compared with 2,2-diphenil-1-picryl hydrazyl method with α-tocopherol as the standard antioxidant. The results showed that the extract of 200 ppm inhibited fatty acids oxidation by 80.40% and IC50 for free radical scavenging was 85.82 ppm. There was no significant different (α = 0.05) inhibition of unsaturated fatty acids oxidation between the sample and α-tocopherol at 200 ppm. This study suggested that the leaves extract of P. crocatum has a potential natural antioxidant.